Chapter Biomarkers in Rare Genetic Diseases - Ferlini, Alessandra (InTechOpen, 2016)
Today, as the need of new regenerative solutions is steadily increasing, the demand for new bio-devices with smart functionality is pushing material scientists to develop new synthesis concepts. Indeed, the conventional approaches for biomaterials fail when it comes to generate nano-biocomposites with designed biomimetic composition and hierarchically organized architecture mimicking biologically relevant tissue features. In this respect, an emerging concept in material science is to draw inspiration from natural processes and products, which we may consider as the most advanced examples of smart nanotechnology. Natural processes of supramolecular assembly and mineralization of organic macromolecules, known as biomineralization, generate complex hybrid 3D constructs that are the basis of skeletons, exoskeletons, nacre and shells. On the other hand, natural structures such as woods and plants exhibit multi-scale hierarchic organization that is the source of smart and anisotropic mechanical properties associated with high porosity and lightness. The association of nature-inspired nano-technological products with smart functionalization can provide new advanced solutions to critical and still unmet clinical needs. In this respect, magnetic activation of biomaterials by the use of a recently developed biocompatible, resorbable magnetic apatite promises to represent a new safe and effective switching tool, enabling personalized applications in regenerative medicine and theranostics that so far were not feasible, due to the cytotoxicity of the currently used magnetic materials.